2021
DOI: 10.1371/journal.pone.0259148
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion After Fibrinolytic Therapy (RAFT): An open-label, multi-centre, randomised controlled trial of bivalirudin versus heparin in rescue percutaneous coronary intervention

Abstract: Background The safety and efficacy profile of bivalirudin has not been examined in a randomised controlled trial of patients undergoing rescue PCI. Objectives We conducted an open-label, multi-centre, randomised controlled trial to compare bivalirudin with heparin ± glycoprotein IIb/IIIa inhibitors (GPIs) in patients undergoing rescue PCI. Methods Between 2010–2015, we randomly assigned 83 patients undergoing rescue PCI to bivalirudin (n = 42) or heparin ± GPIs (n = 41). The primary safety endpoint was any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The incidence of any bleeding was significantly lower in the Bivalirudin group. However, findings from 3 studies namely the BRAVE-4 trial [25], RAFT trial [28], and VALIDATE-SWEDEHEART trial with STEMI cohort [29] showed an increase in bleeding with bivalirudin. Among them, the RAFT trial had significantly higher odds of 2.11 of any bleeding [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of any bleeding was significantly lower in the Bivalirudin group. However, findings from 3 studies namely the BRAVE-4 trial [25], RAFT trial [28], and VALIDATE-SWEDEHEART trial with STEMI cohort [29] showed an increase in bleeding with bivalirudin. Among them, the RAFT trial had significantly higher odds of 2.11 of any bleeding [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, findings from 3 studies namely the BRAVE-4 trial [25], RAFT trial [28], and VALIDATE-SWEDEHEART trial with STEMI cohort [29] showed an increase in bleeding with bivalirudin. Among them, the RAFT trial had significantly higher odds of 2.11 of any bleeding [28]. In a meta-analysis of 18 RCTs including patients treated with bivalirudin vs. heparin during PCI using coronary stents in >50% of patients by Bittl et al ., the risk of any type of bleeding was reduced with bivalirudin therapy compared to heparin therapy (OR = 0.64; 95% CI, 0.53– 0.76) at 30 days [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation